2021
DOI: 10.1002/slct.202004605
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic‐Assisted Ionic Liquid Extraction of Four Biflavonoids from Ginkgo biloba L.

Abstract: In the study, four main biflavonoids (bilobetin (BIL), ginkgetin (GIN), isoginkgetin (IGIN) and sciadopitysin (SCI)) were extracted from Ginkgo biloba L. by ultrasonic-assisted ionic liquid extraction (UAILE). The above four biflavonoids from Ginkgo biloba L. were simultaneously determined by the established high performance liquid chromatography (HPLC) approach. Next, three novel ionic liquids (ILs) were synthesized by onestep method from benzoxazole and three acids or salts. The structure of ILs were charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…A similar high amount of sciadopitysin compared to amentoflavone in leaves was reported by Pandey et al [ 23 ] in ginkgo trees of different ages. The low content of amentoflavone is probably the reason why this biflavonoid was generally not detected in leaves in other studies [ 19 , 21 , 22 ]. Amentoflavone was also the least abundant biflavonoid in the seed parts where biflavonoids were detected in seed petioles and sarcotesta, according to our data.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A similar high amount of sciadopitysin compared to amentoflavone in leaves was reported by Pandey et al [ 23 ] in ginkgo trees of different ages. The low content of amentoflavone is probably the reason why this biflavonoid was generally not detected in leaves in other studies [ 19 , 21 , 22 ]. Amentoflavone was also the least abundant biflavonoid in the seed parts where biflavonoids were detected in seed petioles and sarcotesta, according to our data.…”
Section: Discussionmentioning
confidence: 84%
“…One of the earliest HPLC-DAD methods for separating biflavonoids from ginkgo leaves was developed by Briancon-Scheid et al [ 19 ], the HPLC-DAD method for the simultaneous determination of four (bilobetin, ginkgetin, isoginkgetin, sciadopitysin) biflavonoids. Kaur et al [ 20 ] developed a method for the simultaneous determination of three biflavonoids (bilobetin, sciadopitysin, and ginkgetin) from ginkgo leaves, and recently Lei et al [ 21 ] focused on four biflavonoids (bilobetin, ginkgetin, isoginkgetin, sciadopitysin), as did Wang et al [ 22 ]. Pandey et al [ 23 ] reported only two biflavonoids (amentoflavone and sciadopitysin) in a crude extract of ginkgo leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 provides examples of selected reports on the presence of biflavonoids in various ginkgo plant parts and the used extraction and identification methods. Various organic solvents such as acetone, methanol, ethanol and petroleum ether have been used for the isolation of biflavonoids [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Recent data also show that sustainable extraction technologies [ 43 ] and modern extraction techniques [ 42 ] can be useful for the extraction of biflavonoids from ginkgo.…”
Section: Biflavonoids In Ginkgomentioning
confidence: 99%
“…Various organic solvents such as acetone, methanol, ethanol and petroleum ether have been used for the isolation of biflavonoids [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Recent data also show that sustainable extraction technologies [ 43 ] and modern extraction techniques [ 42 ] can be useful for the extraction of biflavonoids from ginkgo. The method of choice for the separation of compounds is liquid chromatography.…”
Section: Biflavonoids In Ginkgomentioning
confidence: 99%
See 1 more Smart Citation